Derivasi dan Infleksi Bahasa Indonesia dalam Kata Bahasa Inggris di Aplikasi X Periode Januari-Februari 2024 - Nurazizah, Nurazizah; Juansah, Dase Erwin; Iriyansah, Muhammad Rinzat (Aksara: Jurnal Bahasa dan Sastra, 2024)
This research discusses the Indonesian derivation and inflections used in English words with a background based on the large number of social media users who combine English words with Indonesian affixations. The aim is to describe the process of Indonesian derivation and inflection in English words and to describe changes in parts of speech that occur from the original words. The data source used in this research is application application X period January-February 2024 with data collection techniques through free listening techniques, note-taking techniques, and documentation techniques (screen captures). This research method uses a qualitative descriptive method with a morphological approach. The theory used in this research is the theory of derivation and inflection using Baeur's theory and additional theory for explaining the function and meaning of affixation using the theories of Arifin and Junaiyah, Putrayasa, and Kridalaksana. The results of this study found changes in parts of speech in the derivation category of 44%, divided into nine, changes of parts of speech from noun to verb, changes of parts of speech from noun to adjective, a change of parts of speech from noun to adverb, a change of parts of speech from verb to noun, a change of parts of speech from verb to adjective, a change of parts of speech from verb to adverb, a change of parts of speech from adjective to a noun, a change of parts of speech from adjective to the verb, and changes of parts of speech from adjective to adverb. However, in each parts of speech derived from noun, verb, and adjective was not found to be a change to the adverb parts of speech because no Indonesian affixation was found which changed the parts of speech of the English word to the adverb parts of speech. Furthermore, 56% of parts of speech changes in the inflection category are divided into three types, changes of parts of speech from noun to noun, a change of parts of speech from verb to verb, and changes of parts of speech from adjective to adjective.Keywords: language, derivation, inflection, parts of speech, morphology.